2019
DOI: 10.31234/osf.io/gps3h
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social anxiety is associated with alterations in heart rate but not gaze in a real social interaction

Abstract: Much of our current understanding of social anxiety rests on the use of simplistic stimulation material in laboratory settings. Latest technological developments now allow the investigation of eye movements and physiological measures during real interactions with adequate recording quality. Considering the wealth of conflicting findings on gaze behavior in social anxiety, the current study aimed at unraveling the mechanisms contributing to differential gaze patterns in a naturalistic setting in the general pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Thus, high socially anxious individuals tended to look less at other people at a near distance than low socially anxious individuals. See also Hessels, Holleman, Cornelissen, Hooge, and Kemner (2018), who showed that looking behavior in dyadic conversation was related to social anxiety traits, and Rösler, Göhring, Strunz, and Gamer (2020), who showed no relation between social anxiety traits and looking behavior in a waiting room context. Although we have shown in our experiment that consistent differences in looking behavior across participants occur, we cannot attribute this to social anxiety, as we did not assess social anxiety traits.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, high socially anxious individuals tended to look less at other people at a near distance than low socially anxious individuals. See also Hessels, Holleman, Cornelissen, Hooge, and Kemner (2018), who showed that looking behavior in dyadic conversation was related to social anxiety traits, and Rösler, Göhring, Strunz, and Gamer (2020), who showed no relation between social anxiety traits and looking behavior in a waiting room context. Although we have shown in our experiment that consistent differences in looking behavior across participants occur, we cannot attribute this to social anxiety, as we did not assess social anxiety traits.…”
Section: Discussionmentioning
confidence: 99%